2008
DOI: 10.1099/ijs.0.65668-0
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplasma phylogenetics based on analysis of secA and 23S rRNA gene sequences for improved resolution of candidate species of 'Candidatus Phytoplasma'

Abstract: Phytoplasma phylogenetics has focused primarily on sequences of the non-coding 16S rRNA gene and the 16S-23S rRNA intergenic spacer region (16-23S ISR), and primers that enable amplification of these regions from all phytoplasmas by PCR are well established. In this study, primers based on the secA gene have been developed into a semi-nested PCR assay that results in a sequence of the expected size (about 480 bp) from all 34 phytoplasmas examined, including strains representative of 12 16Sr groups. Phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(142 citation statements)
references
References 31 publications
2
135
1
4
Order By: Relevance
“…Worldwide there are other reports of this phytoplasma group mainly on ornamental Cactaceae in countries such as: China (Accession # EF190970) (Wei et al, 2007;Cai et al, 2008), even in Mexico (Acc. # AF356846) (IRPCM, 2004;Leyva-López et al, 1999); UK (Aster yellows Cactus) (Lee et al, 1998) and in USA (Cactus aster yellows) (Hodgetts et al, 2008). On Opuntia crop, in USA a 16SrI-B phytoplasma subgroup was identified on a fruit of O. ficus-indica (Bertaccini et al, 2007) and this 16SrI phytoplasma group agrees with our results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Worldwide there are other reports of this phytoplasma group mainly on ornamental Cactaceae in countries such as: China (Accession # EF190970) (Wei et al, 2007;Cai et al, 2008), even in Mexico (Acc. # AF356846) (IRPCM, 2004;Leyva-López et al, 1999); UK (Aster yellows Cactus) (Lee et al, 1998) and in USA (Cactus aster yellows) (Hodgetts et al, 2008). On Opuntia crop, in USA a 16SrI-B phytoplasma subgroup was identified on a fruit of O. ficus-indica (Bertaccini et al, 2007) and this 16SrI phytoplasma group agrees with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Some of these were ornamentals such as Opuntia monacantha in Lebanon (Choueiri et al, 2005); and Opuntia sp. and Zygocactus truncatus in China (Cai et al, , 2008, and on Cactus in USA (Hodgetts et al, 2008). Also in Mexico phytoplasmas were associated with ornamental cacti such as Echinopsis subdenudata and Opuntia sp.…”
Section: Introductionmentioning
confidence: 99%
“…phytoplasma associated with K. arvensis phyllody in Italy [18] and almond witches'-broom in Iran [21]. The 23S rRNA gene has not been sequenced completely for most of the phytoplasmas [10,12]. Our study of complete 23S rRNA gene sequence from TP phytoplasma showed that it has maximum identity with Jujube witches'-broom phytoplasmas of 16SrV group.…”
Section: Discussionmentioning
confidence: 94%
“…For amplification of secA gene, SecAfor1/SecArev3 (5 0 -GARATGAA AACTGGRGAAGG-3 0 /5 0 -GTTTTRGCAGTTCCTGTCAT NCC-3 0 ) phytoplasma universal primers were used [12]. PCR was also performed using 16SrIX group specific primer pair rp(IX)F2/rp(IX)R2 (5 0 -GCACAAGCTATTTTAA TGTTTACACC-3 0 /5 0 -CAAAGGGACTAAACCTAAAG-3 0 ) for amplification of a part of ribosomal protein (rp) gene.…”
Section: Isolation Of Total Dna and Pcr Amplificationmentioning
confidence: 99%
See 1 more Smart Citation